Protective effects of palm tocotrienol against glucocorticoid induced osteoporosis via regulation of gene expressions - Elvy Suhana Mohd Ramli,; Fairus Ahmad,; Norazlina Mohamed,; Mohamad Fairuz Yahaya,; Ima Nirwana Soelaiman, (Pusat Perubatan Universiti Kebangsaan Malaysia, 2018)
Long term glucocorticoids administration induces oxidative stress which leads to alteration of bone structure and strength. Palm oil is rich in tocotrienol, an antioxidant. It can be used for the prevention of oxidative stress related diseases. The main objective of this study was to determine the mechanism of palm tocotrienol in maintaining the bone structure and strength in glucocorticoidinduced osteoporosis. Thirty two adult male Sprague-Dawley rats, aged 3 months, weighing 300-320 g rats were used in this study. Sixteen rats undergone adrenalectomy and were administered with 120μg/kg/day intramuscular injection of dexamethasone. Eight rats were supplemented with oral palm tocotrienol 60 mg/kg/day (Adrx+Dex+PTT) and the other eight rats were given oral vehicle palm olein 0.1 ml/kg/day (Adrx+Dex). Eight rats underwent sham procedure and were given vehicle palm olein 0.05 ml/kg/day by intramuscularly and oral 0.1 ml/kg/day (Sham). The rats were euthanized after two months of treatments. Eight rats were euthanized after acclimatic action without receiving any treatment (Baseline). The right femurs were used for bone biomechanical strength and histomorphometry analysis while the left for gene expression and oxidative stress enzymes activities. The results indicated that long-term glucocorticoid treatment significantly increased bone resorption marker, CTX (6060.7 ± 410 pg/ml) and decreased bone structure and strength. Osteoblast and osteoclast related genes expressions indicated an increase in bone turnover. Supplementation of palm tocotrienol had maintained serum resorption (2619.4 + 209 pg/ml) marker level and preserved bone structure and strength. Gene expression analysis showed decrease in bone resorption. The findings suggested that palm tocotrienol has potential benefits against glucocorticoid-induced osteoporosis by regulating osteoblast and osteoclast related gene expressions.